2001
DOI: 10.1002/1099-0771(200101)14:1<1::aid-bdm361>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Social cues and verbal framing in risky choice

Abstract: We examined how people use social and verbal cues of di}ering priorities in making social decisions[ In Experiment 0\ formally identical lifeÐdeath choice problems were presented in di}erent hypothetical group contexts and were phrased in either a positive or negative frame[ The risk!seeking choice became more domi! nant as the number of kin in an endangered group increased[ Framing e}ects occurred only in a heterogeneous group context where the lives at risk were a mixture of kin and strangers[ No framing e}e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 23 publications
0
24
0
2
Order By: Relevance
“…Wang and Johnston, 1995;Wang et al, 2001). A social phenomenon in financial markets is, for instance, herding, which refers to the behavior that investors are influenced by other investors' decisions.…”
Section: Investment Decision-making Under Conditions Of Uncertaintymentioning
confidence: 61%
“…Wang and Johnston, 1995;Wang et al, 2001). A social phenomenon in financial markets is, for instance, herding, which refers to the behavior that investors are influenced by other investors' decisions.…”
Section: Investment Decision-making Under Conditions Of Uncertaintymentioning
confidence: 61%
“…A low degree of value, like those for the animal scenarios in the neutral condition in this study, the alien condition of the Wang et al (2001) study, and the culpable AIDS patients condition of the Levin and Chapman (1990) study, results in frame failing to affect choice, and in preferences near neutral or risk averse in both frames. This situation, as mentioned above, may be explained by the relationship between participants' value for the group at stake and the shape of the value function.…”
Section: Discussionmentioning
confidence: 99%
“…Wang, Simons, and Brédart (2001) found significant framing effects for human lives (36% choice of the risky option in the positive frame, 66% in the negative frame) but no difference in the preference for the risky option between frames for extraterrestrial lives (52% choice of the risky option in both frames). They suggested that participants lacked an aspiration for saving alien lives, as opposed to human lives, and that this led to near neutral choices in both frames.…”
Section: Valuementioning
confidence: 99%
See 1 more Smart Citation
“…진화 수용에 관한 의사결정에서 지식이 아닌 앎에 대한 주관적 느낌에 근거한다는 Ha et al(2012) (Walton, 1999). 인지편향은 유아기 에 발달심리학적으로 나타나기 시작하지만 사회적 활동을 통하여 강 화되는 특성도 보고되고 있으므로 교정을 위한 가장 효율적인 방법은 성장기의 교육을 통해서 일 것이다 (Wang et al, 2001). 최근 탈인지편 향에 대한 훈련전략을 연구하는 Morewedge et al(2015) (Hodgson, 2004).…”
Section: 인지편향은 생득적으로 형성되어 있는 인간의 사고 습관이며 교정unclassified